Pengembangan Tutorial Pembelajaran operasi Hitung Berbasis Teknologi Informasi Untuk Siswa Tunagrahita - Renny Sulistyowati; Henry Praherdhiono (Department of Special Education, 2015)
Occasionally, students with intellectual disability are difficult to understand the abstract concept especially in Mathematics. This research aims to develop tutorial media by using Information Technology in Arithmetic Operation for 4th Grade Elementary school students. This research uses Hannafin and Peck model. Product in this research is a learning tutorial using Information Technology for 4th Grade Elementary students who have mental retardation. This product has observed to the media expert, material expert, and students. The result of this research showed that tutorial media using Information Technology is very suitable and appropriate to be implemented in arithmetic learning.Siswa tunagrahita sulitan memahami konsep yang bersifat abstrak khususnya matematika. Dasar tujuan Penelitian adalah guna mengembangkan media tutorial berbasis teknologi informasi operasi hitung kelas IV siswa tunagrahita. Model yang digunakan dalam penelitian adalah pengembangan Hannafin dan Peck. Hasil atau produk yang akan diperoleh adalah sebuah tutorial pembelajaran berbasis teknologi informasi yang berfungsi menjadi media untuk pembelajaran operasi hitung kelas IV tunagrahita. Produk diuji cobakan kepada ahli media, ahli materi dan siswa. Hasil uji coba menunjukkan bahwa media tutorial berbasis teknologi informasi secara umum layak difungsikan pada kegiatan belajar operasi hitung.